2012
DOI: 10.1186/1472-6963-12-226
|View full text |Cite
|
Sign up to set email alerts
|

Reasons behind non-adherence of healthcare practitioners to pediatric asthma guidelines in an emergency department in Saudi Arabia

Abstract: BackgroundThe prevalence of childhood bronchial asthma in Saudi Arabia has increased in less than a decade from 8% to 23%. Innovations in the management of asthma led to the development of evidence based clinical practice guidelines and protocols to improve the patients’ outcomes. The objectives of this study are to examine the compliance of the healthcare providers in the Pediatrics Emergency Department, in King Khalid University Hospital, with the recommendations of the Pediatrics Asthma Management Protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Another study in our institute investigated the barriers that faced the implementation of 1 CPG at KKUH and identified several barriers including organizational barriers (eg, staff and bed shortage, deficient outpatient referral system, and availability and cost of certain devices), CPG intrinsic barriers (eg, lack of clear dissemination and implementation strategies and lack of recommendations suitable for the characteristics of some patients), and health care provider barriers (eg, attitudes and beliefs of providers, language barrier between nurses and parents, lack of awareness and familiarity with the CPGs, and disagreement with some recommendations). 11,31 In this study, we used the FMEA in the pre-implementation phase of the CPG at our institution. This The strength of this study comes from the fact that it is the first to use FMEA as an approach to enhance CPGI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study in our institute investigated the barriers that faced the implementation of 1 CPG at KKUH and identified several barriers including organizational barriers (eg, staff and bed shortage, deficient outpatient referral system, and availability and cost of certain devices), CPG intrinsic barriers (eg, lack of clear dissemination and implementation strategies and lack of recommendations suitable for the characteristics of some patients), and health care provider barriers (eg, attitudes and beliefs of providers, language barrier between nurses and parents, lack of awareness and familiarity with the CPGs, and disagreement with some recommendations). 11,31 In this study, we used the FMEA in the pre-implementation phase of the CPG at our institution. This The strength of this study comes from the fact that it is the first to use FMEA as an approach to enhance CPGI.…”
Section: Resultsmentioning
confidence: 99%
“…Research groups worldwide have studied trends in implementation and suggested that CPGI requires the use of different measures including assessment framework, implementation‐planning checklist, revised taxonomy of implementation strategies, and implementation tools . The CPG programs in the Middle East (eg, Bahrain, United Arab Emirate, Oman and other programs in Riyadh and Jeddah, Saudi Arabia), albeit of a limited experience, have used the previous measures but not the Failure Mode and Effect Analysis (FMEA) to enhance the implementation process . FMEA is defined as “a systematic, proactive method for evaluating a process to identify where and how it might fail and to assess the relative impact of different failures, in order to identify the parts of the process that are most in need of change.” FMEA may be performed to improve a system, design, and/or a process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two papers explicitly stated that they used theory to explore barriers and enablers; using a conceptual model of the innovation in diffusion theory18 to analyse the results of focus groups and to determine the barriers to implementation of a paediatric asthma management protocol19 and the Cabana taxonomy20 to assess barriers to behaviour change for the appropriate use of tissue plasminogen activator (tPA) in ischemic stroke 21…”
Section: Resultsmentioning
confidence: 99%
“…12 Resistance of health professionals toward guideline adherence appears unanimous in the literature. [27][28][29] Health professionals are in need of simple, current, reliable, and accessible guidelines, 28 while, in parallel, the demand for training health professionals in guideline usage becomes a priority. 30 Additionally, a recent systematic review 31 highlighted the issue of sustainability of professionals' adherence to clinical practice guidelines, with the majority of professionals abandoning guideline usage, a year after being familiar with the recommendations.…”
Section: Semicyuc-senpe 21mentioning
confidence: 99%